Research on packet scheduling in input-queued switches - XIONG Qing-xu (Tongxin xuebao)
The packet scheduling issues in VOQ, CIOQ and CICQ architecture switches were surveyed, respectively, from the view of coordinating, reducing and isolating the conflicts of arbitration of input and output contention. The qualitative analysis and quantificational comparisons of the popular algorithms were given, and some special issues were pointed out. The packet scheduling in electronic-optical switches was also discussed. Finally the future research work and directions were explored from the view of switch architecture and scheduling algorithm, respectively.